Human Resources Aspects in Mosque Financial Management in Jogokariyan Mosque and Al-Ikhlash Jatipadang Mosque - Fauzan, Arif Fauzan; Zakaria, Zainal Arifin; Siregar, Saparuddin (International Journal Ihya' 'Ulum al-Din, 2024)
Indonesia has the largest Muslim population in the world and is a generous country in the world in donating money through mosques. From here, mosque administrators/takmirs need to build, maintain, and increase the trust given by the congregation to the mosque, especially in improving services and increasing access to the impact of donations given by the congregation. In this case, human resources are the highest asset in mosque management. This research aims to make human and financial resource management more transparent and accountable and able to have a big impact on society. This research method is descriptive qualitative with the analytical tool used, namely ANP (Analytic Network Process) with a total of 7 respondents; the research objects are the Jogokariyan Mosque, Yogyakarta, and the Al-Ilhlash Mosque, Jatipadang, Jakarta. The data collection results show that human resources in the two mosques have high problems. The results of the analytical synthesis of the network process of internal problems, problems, and solutions for human resources and management. In the internal problems cluster, the integrity aspect was chosen as a priority issue in managing mosque finances with a score of (0.331), followed by the accountability aspect with a score of (0.240), and the human resources aspect (0.215).